2016
DOI: 10.4049/jimmunol.1500619
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Suppress CCR9-Mediated Chemotaxis, Calcium Flux, and Adhesion to MAdCAM-1 in Human T Cells

Abstract: CCR9 expressed on T lymphocytes mediates migration to the small intestine in response to a gradient of CCL25. CCL25-stimulated activation of α4β7 integrin promotes cell adherence to mucosal addressin cell adhesion molecule-1 (MAdCAM-1) expressed by vascular endothelial cells of the intestine, further mediating gut-specific homing. Inflammatory bowel disease is a chronic inflammatory condition that primarily affects the gastrointestinal tract and is characterized by leukocyte infiltration. Glucocorticoids (GCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The biological role of the CCR9-CCL25 axis and the evidence implicating CCR9, and CCL25 in gut inflammation in both human and murine IBD, suggest this is an appropriate pathway to target therapeutically. 10 , 29 , 39 , 50 , 51 However, the involvement of CCR9 and CCL25 in immune regulation and tolerance raises valid concerns that under some circumstances inhibition could be detrimental. Studies of immunoblockade of CCR9 and CCL25 in the Samp1/Yit model, showing an effect on early but not late inflammation, suggest that timing of intervention may also be important, with the possibility of a role in preventing or inducing rather than maintaining remission.…”
Section: Ccr9 and Ccl25mentioning
confidence: 99%
“…The biological role of the CCR9-CCL25 axis and the evidence implicating CCR9, and CCL25 in gut inflammation in both human and murine IBD, suggest this is an appropriate pathway to target therapeutically. 10 , 29 , 39 , 50 , 51 However, the involvement of CCR9 and CCL25 in immune regulation and tolerance raises valid concerns that under some circumstances inhibition could be detrimental. Studies of immunoblockade of CCR9 and CCL25 in the Samp1/Yit model, showing an effect on early but not late inflammation, suggest that timing of intervention may also be important, with the possibility of a role in preventing or inducing rather than maintaining remission.…”
Section: Ccr9 and Ccl25mentioning
confidence: 99%
“…Glucocorticoids have direct effects on osteoblast, osteocyte, and osteoclast function resulting in reduced bone remodeling and diminished repair of microdamage to bone. In addition to the direct effects on bone cells, glucocorticoids also have effects on the intestine, kidneys, gonads, and probably parathyroid glands, which may contribute to osteoporosis 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutical blockade of T-cell homing via the integrin α4β7 and the cellular adhesion molecule MAdCAM-1 has been intensively studied during the last years as T cells represent a key player in the perpetuation of intestinal inflammation[67]. Most recent work by Wendt et al[68] demonstrated that even classic glucocorticoids act partially via MAdCAM-1 by reducing C-C chemokine receptor type 9-mediated chemotaxis of T-lymphocytes. Agents targeting leukocyte trafficking have been developed and some anti-integrin antibodies are already available for IBD therapy while others will follow in the near future[69].…”
Section: Discussionmentioning
confidence: 99%